2022
DOI: 10.2147/dmso.s374784
|View full text |Cite
|
Sign up to set email alerts
|

STAMP2 Attenuates Cardiac Dysfunction and Insulin Resistance in Diabetic Cardiomyopathy via NMRAL1-Mediated NF-κB Inhibition in Type 2 Diabetic Rats

et al.

Abstract: Background Previous studies have reported that six transmembrane protein of prostate 2 (STAMP2) attenuates metabolic inflammation and insulin resistance in diabetes mellitus. However, the role of STAMP2 in the diabetic heart is still unclear. Methods A diabetic rat cardiomyopathy model was established via intraperitoneal STZ injection. STAMP2 was overexpressed in the treatment group using adeno-associated virus. Rat heart diastolic function was measured using echocardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Studies had shown that KCNJ2 [136], ARG1 [137], TLR4 [138], IFIH1 [139], FBN2 [140], PDK4 [141], TLR8 [142], PDGFC (platelet derived growth factor C) [143], FNIP1 [144], TLR2 [145], PTPN11 [146], LATS2 [147], GCH1 [148], ARFGEF2 [149], CA2 [150], PTPRC (protein tyrosine phosphatase receptor type C) [151], CCR2 [152], GAB1 [153], VEGFA (vascular endothelial growth factor A) [154], UBR1 [155], PHLPP1 [156], MTM1 [157], FMR1 [158], SIRT1 [159], NOD2 [160], MYOF (myoferlin) [161], OSBPL11 [162], ZBTB11 [121], UTRN (utrophin) [163], ZNF593 [164], CCR7 [165], PRDX2 [166], BIN1 [167], NFIC (nuclear factor I C) [168], TCF4 [169], PPP1R13L [124], NDUFB11 [170], TAX1BP3 [171], TRPM4 [172], NMRAL1 [173], LGALS3 [126] and NAA10 [174] were associated with cardiomyopathy. CD274 [175], CEACAM1 [176], STAT1 [177], ARG1 [178], TLR4 [179], LRRK2 [180], ABCA1 [181], IFIH1 [182], TLR5 [183], PTGS2 [184], CYP2D6 [185], RNF213 [186], C9ORF72 [187], JAK2 [188], TLR8 [189], NOTCH2 [190], PDGFC (platelet derived growth factor C) [191], TLR2 [192], PRKAB2 [193], HDAC9 [194], NCOA4 [195], LATS2 [196], DICER1 [197], IL1RN [198], GCH1 [148], EGR1 [199], HIPK3 [200], ZEB2 [201], HIF1A [202], PLA2G7 [203], DOCK8 [204], CCR2 [205], PPP1R15B [206], GCLC (...…”
Section: Discussionmentioning
confidence: 99%
“…Studies had shown that KCNJ2 [136], ARG1 [137], TLR4 [138], IFIH1 [139], FBN2 [140], PDK4 [141], TLR8 [142], PDGFC (platelet derived growth factor C) [143], FNIP1 [144], TLR2 [145], PTPN11 [146], LATS2 [147], GCH1 [148], ARFGEF2 [149], CA2 [150], PTPRC (protein tyrosine phosphatase receptor type C) [151], CCR2 [152], GAB1 [153], VEGFA (vascular endothelial growth factor A) [154], UBR1 [155], PHLPP1 [156], MTM1 [157], FMR1 [158], SIRT1 [159], NOD2 [160], MYOF (myoferlin) [161], OSBPL11 [162], ZBTB11 [121], UTRN (utrophin) [163], ZNF593 [164], CCR7 [165], PRDX2 [166], BIN1 [167], NFIC (nuclear factor I C) [168], TCF4 [169], PPP1R13L [124], NDUFB11 [170], TAX1BP3 [171], TRPM4 [172], NMRAL1 [173], LGALS3 [126] and NAA10 [174] were associated with cardiomyopathy. CD274 [175], CEACAM1 [176], STAT1 [177], ARG1 [178], TLR4 [179], LRRK2 [180], ABCA1 [181], IFIH1 [182], TLR5 [183], PTGS2 [184], CYP2D6 [185], RNF213 [186], C9ORF72 [187], JAK2 [188], TLR8 [189], NOTCH2 [190], PDGFC (platelet derived growth factor C) [191], TLR2 [192], PRKAB2 [193], HDAC9 [194], NCOA4 [195], LATS2 [196], DICER1 [197], IL1RN [198], GCH1 [148], EGR1 [199], HIPK3 [200], ZEB2 [201], HIF1A [202], PLA2G7 [203], DOCK8 [204], CCR2 [205], PPP1R15B [206], GCLC (...…”
Section: Discussionmentioning
confidence: 99%
“…114,117 IKK/NF-κB signal pathway was involved in IR in DM. 115,118 In DCM, activating PI3K/AKT signal pathway or inhibiting NF-κB signal pathway could reduce the occurrence of IR, 119,120 and AKT2 deficiency resulted in severe glucose intolerance, myocardial contractile dysfunction, cardiomyocyte apoptosis, and impaired cardiac function. 121,122 IRS1/PI3K/AKT pathway was the main signal regulation pathway of podocyte IR, and blocking this pathway would induce EMT and glomerulosclerosis in DN podocytes.…”
Section: Impaired Insulin Signaling Pathwaysmentioning
confidence: 99%
“…Studies, both preclinical and clinical, have shown that DM induces a pro-fibrotic state. Four-week-old male Sprague–Dawley rats with streptozocin-induced DM exhibited a higher collagen type I and III accumulation compared to the control group [ 62 ]. Critically, a recently published systematic review and meta-analysis of 32 studies by Salvador et al highlighted a relationship between DM and a higher degree of myocardial fibrosis assessed by either the histological collagen volume fraction (mean difference 5.80; 95% CI: 2.00–9.59) or extracellular volume fraction (mean difference: 2.09; 95% CI: 0.92–3.27) [ 63 ].…”
Section: The Role Of Diabetes Mellitus In Heart Failure Pathophysiologymentioning
confidence: 99%